THE STUDENTS PERSONALITY BASED ON THE READING STRATEGY USED - Nurteteng Syaid (Universitas Muhammadiyah Makassar, 2018)
The study attempts to analyze the students’ personality, the reading strategy that the students used in reading, and the correlation between the students personality and reading strategy used. The study took place at SMAN 6 Wajo where 3 classes were participated to represent their classes. The study employed descriptive method, where the data obtained through personality inventory questionnaire, reading strategy questionnaire and reading test. There are three points were found from this reserach. First, regarding with the students personality, mostly students in SMAN 6 Wajo are extrovert persons. The rest of students is dominated with introvert personality. Second, the reading strategy that the student most frequently used is Global Reading Strategy. It is followed with Problem Solving Strategy and Support Reading Strategy. Last, related with the relationship between reading strategy used and the students personality, there are three points we got from this study. Fisrt, Global Reading Strategy is commonly used by extrovert students. Second, Problem Solving Strategy is used by introvert students. Third, Support Reading Strategy is used by thinking students.